POLITIK DAN ISU EKONOMI, GENDER, KELAS, DAN RAS DALAM NOVEL 1984 KARYA GEORGE ORWELL - Riffa Taufik Hidayatullah; Sara Samrotul Atkia; Nurholis Nurholis (Cahaya Ilmu Bangsa Institute, 2024)
Abstrak Novel